A redefinition of Iranothyas Bader, 1984 with the description of a new species from Oman - Pesic, Vladimir; Gerecke, Reinhard; Smit, Harry (Zootaxa, 2009)
From a reinvestigation of the holotype of Iranothyas circularis (Schwoerbel & Sepasgozarian, 1976) results that this species was based on a female, not a male, as stated in the original description. The genus Iranothyas Bader, 1984, is redefined and Balaneothyas Gerecke, 1999 (monotypic, type species: B. marismortui Gerecke, 1999 from Israel) is recognized as its junior synonym. Bader's (1984) proposal to attribute Panisopsis orientalis Imamura & Mitchell, 1967 to Iranothyas is refused. A new, third species of Iranothyas, I. alhajarica n. sp., is described from Oman.